1996
DOI: 10.1073/pnas.93.26.15024
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone activity and structure of monomeric polypeptide binding domains of GroEL

Abstract: The chaperonin GroEL is a large complex composed of 14 identical 57-kDa subunits that requires ATP and GroES for some of its activities. We find that a monomeric polypeptide corresponding to residues 191 to 345 has the activity of the tetradecamer both in facilitating the refolding of rhodanese and cyclophilin A in the absence of ATP and in catalyzing the unfolding of native barnase. Its crystal structure, solved at 2.5 Å resolution, shows a well-ordered domain with the same fold as in intact GroEL. We have th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
136
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 39 publications
12
136
1
Order By: Relevance
“…In addition, it has been observed that folding of hen lysozyme can be promoted by GroEL alone, in the absence of GroES and ATP (20). Similar results have been demonstrated for barnase (21) and for rhodanese (22).…”
supporting
confidence: 88%
“…In addition, it has been observed that folding of hen lysozyme can be promoted by GroEL alone, in the absence of GroES and ATP (20). Similar results have been demonstrated for barnase (21) and for rhodanese (22).…”
supporting
confidence: 88%
“…For example, functionally active monomeric minichaperones containing part of the polypeptide binding domain of GroEL are known to be effective in vitro and in vivo. 32,33 Also monomeric Cpn60 from Thermus thermophilus has been shown to possess the ability to suppress aggregation and promote protein folding with no requirement for ATP or GroES. 34 Thus, M. tuberculosis Cpn60s in a similar fashion might have evolved to function in lower oligomeric state with no ATP requirement.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all ERp57 residue numbers refer to the human sequence after cleavage of the predicted signal peptide to generate the mature N terminus beginning with the sequence Ser 1 -Asp 2 -Val 3 . Gene products encoding the a and a domains were amplified by PCR and cloned into a pRSET A-derived E. coli expression vector (35). Protein expression from this vector results in the production of a fusion protein with an N-terminal 17-amino acid affinity tag containing a hexahistidine sequence.…”
Section: Methodsmentioning
confidence: 99%